2018
DOI: 10.3892/etm.2018.7110
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokines tumor necrosis factor‑α, interleukin‑8 and sleep monitoring in patients with obstructive sleep apnea syndrome

Abstract: The present study investigated the changes of tumor necrosis factor-α (TNF-α), interleukin-8 (IL-8) and sleep ability in patients with obstructive sleep apnea hypopnea syndrome (OSAHS). A total of 684 patients who were admitted to Xuzhou Central Hospital between June 2012 and June 2016 were enrolled to serve as the experimental group and 192 healthy subjects were selected as the control group. Polysomnography was performed on both groups, and serum TNF-α and IL-8 levels were measured by ELISA. Pearson's correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 21 publications
1
39
0
Order By: Relevance
“…As regards AHI and TNF-α levels, Kanbay et al [41] and others [16,78] reported a significant positive correlation between a higher AHI and higher serum TNF-α levels.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…As regards AHI and TNF-α levels, Kanbay et al [41] and others [16,78] reported a significant positive correlation between a higher AHI and higher serum TNF-α levels.…”
Section: Discussionmentioning
confidence: 94%
“…The present results have clinical importance because elevated serum and plasma TNF-α levels can be a risk factor for the development of further systemic diseases in adults with OSAS. Further, more generally, inflammation may play a crucial role in the pathogenesis of OSAS, and there is evidence that individuals with OSAS have elevated interleukin TNF-α [16,29,40,41,45,48,62,78]. These conclusions also have practical importance because, in addition to routine checks on sleep and sleep-disordered breathing, both children and adults with OSAS need a thorough monitoring of their immune systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some, but not all studies, OSA patients also show modest increases in IL6 [52-58]. CPAP treatment of OSA patients was most often, but not always, associated with normal levels of these cytokines similar to the levels in control subjects [52,[59][60][61][62][63][64][65][66][67][68][69]. The normal levels of TNF and IL6 observed in most OSA patients receiving airways therapy and the generally protective role of airways therapy to patient health strongly support the idea that chronic intermittent hypoxia induces inflammatory cytokines that are causal to neuroinflammation and ND.…”
Section: Introductionmentioning
confidence: 99%